A novel control scheme for voltage multiplier based X-ray power supply - Iqbal, Shahid; Besar, Rosli; Venkataseshaiah, C. (2008)
In this paper, a novel dual-mode control scheme for phase-shifted PWM series resonant inverter fed voltage multiplier based X-ray power supply is proposed. The output voltage of the power supply is controlled by varying the phase-shift between inverter switches. In order to achieve quick rise of output voltage, the power supply is started with zero phase-shift and as the output voltage reaches 90% of the target voltage, the phase-shift is increased to a value which corresponds to target output voltage to prevent overshoot. The proposed control scheme has been shown to have excellent performance. Experimental results based on the scaled-down laboratory prototype are presented to validate the effectiveness of proposed dual-mode phase shift modulation control scheme.